2021
DOI: 10.1093/jac/dkab061
|View full text |Cite
|
Sign up to set email alerts
|

No barrier to care, yet disparities in the HIV care continuum in France: a nationwide population study

Abstract: Objectives Even in an ‘optimal’ health system, patients’ characteristics may have an impact on their care. We investigated whether age, gender and place of birth have an impact in the HIV care continuum in France, a country with a universal free healthcare system. Methods We estimated differences in the 5 year restricted mean percentage of person-time spent (i) in care, (ii) receiving ART and (iii) on ART and virally suppress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…These empirical observations are corroborated by several published data. [14][15][16][17][18][19][20][21][22][23][24] Favoring PIs has the advantage of reducing the risk of emerging resistance in the event of poor compliance, because of the high genetic barrier of this class. Conversely, this choice could have a negative impact because of the poorer overall tolerance of PIs compared to INSTIs, 29,30 which is potentially compounded by taking 3 tablets instead of 1 (in France, no single tablet regimen including PIs is available).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These empirical observations are corroborated by several published data. [14][15][16][17][18][19][20][21][22][23][24] Favoring PIs has the advantage of reducing the risk of emerging resistance in the event of poor compliance, because of the high genetic barrier of this class. Conversely, this choice could have a negative impact because of the poorer overall tolerance of PIs compared to INSTIs, 29,30 which is potentially compounded by taking 3 tablets instead of 1 (in France, no single tablet regimen including PIs is available).…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have reported that migrants living with HIV frequently have poor HIV clinical outcomes in comparison with native-born persons. 8 These outcomes included higher frequency of AIDS status and lower CD4 T-cell count at entry into HIV care [9][10][11][12][13] and higher risk of loss to follow-up (LFU), [14][15][16][17] poor ART adherence, and a high risk of virologic failure once in care. [18][19][20][21][22][23][24] These poor results could be mainly because of socio-economic barriers, including difficulties with administrative procedures, finding a job and housing, and difficulties in understanding the health care system.…”
Section: Introductionmentioning
confidence: 99%